Politics in Indonesia: democracy, social networks and youth political participation - Rachmah Ida; Mustain Mashud; Muhammad Saud; Farhan Navid Yousaf; Asia Ashfaq (Cogent Social Sciences)
Social networks have a wider influence on youth political participation, providing the opportunity to remain actively engaged in socio-political issues aiming for good governance in Indonesia. The study highlights the pertinent role of social networks, social ties, and trends in increasing participation among youngsters in Indonesia’s political spheres. The study uses quantitative research to gather data from university students. Social networks indeed have a significant influence created a more engaged and informed generation of youth using social networks to voice their opinions and participate in political activities. The findings show that youth integrate with others through social networks to participate in politics, and this participation has increased political efficacy. Furthermore, a democratic society is a unit that provides network ties for youth-enhancing involvement in political activities. However, it is important to note that social networks alone are insufficient to ensure good governance in Indonesia. Ultimately, online and offline engagement is needed to create a truly participatory and inclusive democracy in Indonesia.